Pengembangan Media Pop Up Book Ekorama untuk Meningkatkan Pemahaman Konsep IPA Kelas V SD - Nuri Alfitriyani; Nirwana Anas (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
The purpose of this study was to focus on the development and feasibility testing of the Ekorama Pop-Up Book as a learning medium, as well as to assess its practicality and effectiveness in helping fifth-grade elementary school students master science concepts related to food chains. Research and Development (R&D) using the ADDIE model—which begins with analysis and ends with evaluation—will be applied in this study. The participants include media and content experts, teachers, and 19 fifth-grade students at MIN 8 in Medan. Data were collected using response questionnaires, concept comprehension tests, and validation sheets. The results of the expert validation indicated that the category was highly valid, highly practical (96.7%), and highly effective (N-Gain = 0.87), as evidenced by the test results showing an increase in students’ understanding. In other words, the Ekorama Pop-Up Book was deemed suitable as a science learning medium for improving conceptual understanding among elementary school students.